Pemphigus Vulgaris Persistently Localized to the Nose with Local and Systemic Response to Topical Steroids - Connie Zhang; Ilana Goldscheider; Thomas Ruzicka; Miklós Sárdy (Medical Journals Sweden, 2017)
Abstract is missing (Short communication)